Neonatal Citalopram Treatment Inhibits the 5-HT Depleting Effects of MDMA Exposure in Rats - Schaefer, Tori L. (American Chemical Society, 2011)
[Image: see text] Neonatal exposure to 3,4-methylenedioxymethamphetamine (MDMA) produces long-term learning and memory deficits and increased anxiety-like behavior. The mechanism underlying these behavioral changes is unknown, but we hypothesized that it involves perturbations to the serotonergic system as this is the principal mode of action of MDMA in the adult brain. During development, 5-HT is a neurotrophic factor involved in neurogenesis, synaptogenesis, migration, and target region specification. We have previously shown that MDMA exposure (4 × 10 mg/kg/day) from postnatal day (P)11–20 (analogous to human third trimester exposure) induces ∼50% decreases in hippocampal 5-HT throughout treatment. To determine whether MDMA-induced 5-HT changes are determinative, we tested if these changes could be prevented by treatment with a selective serotonin reuptake inhibitor (citalopram: CIT). In a series of experiments, we evaluated the effects of different doses and dose regimens of CIT on MDMA-induced 5-HT depletions in three brain regions (hippocampus, entorhinal cortex, and neostriatum) at three time points (P12, P16, P21) during the treatment interval (P11–20) known to induce behavioral alterations when animals are tested as adults. We found that 5 mg/kg CIT administered twice daily significantly attenuated MDMA-induced 5-HT depletions in all three regions at all three ages but that the protection was not complete at all ages. Striatal dopamine was unaffected. We also found increases in hippocampal NGF and plasma corticosterone following MDMA treatment on P16 and P21, respectively. No changes in BDNF were observed. CIT treatment may be a useful means of interfering with MDMA-induced 5-HT reductions and thus permit tests of the hypothesis that the drug’s cognitive and/or anxiety effects are mediated through early disruptions to 5-HT dependent developmental processes.